2005
DOI: 10.1152/ajpregu.00632.2004
|View full text |Cite
|
Sign up to set email alerts
|

Medullary lateral tegmental field: control of respiratory rate and vagal lung inflation afferent influences on sympathetic nerve discharge

Abstract: Phillips, Shaun W., Gerard L. Gebber, and Susan M. Barman. Medullary lateral tegmental field: control of respiratory rate and vagal lung inflation afferent influences on sympathetic nerve discharge. Am J Physiol Regul Integr Comp Physiol 288: R1396 -R1410, 2005. First published December 16, 2004; doi:10.1152/ajpregu.00632.2004.-We used spectral analysis and event-triggered averaging to determine the effects of chemical inactivation of the medullary lateral tegmental field (LTF) on 1) the relationship of intra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
29
1

Year Published

2005
2005
2022
2022

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(35 citation statements)
references
References 56 publications
5
29
1
Order By: Relevance
“…Specifically, blockade of N-methyl-Daspartate (NMDA) receptors in the LTF significantly reduced baroreceptor-mediated inhibition of SND and the cardiacrelated rhythm in SND (26), whereas blockade of non-NMDA EAA receptors reduced the increases in SND produced by activation of arterial chemoreceptors and electrical stimulation of afferents in the cervical vagus nerve (27). Also, we showed that chemical inactivation of the LTF with microinjection of muscimol eliminated the component of SND time-locked to intratracheal pressure (ITP, an index of vagal lung inflation afferent activity) without disrupting the entrainment of phrenic nerve activity (PNA) to ITP (29). These data led us to postulate that the LTF was involved in mediating changes in SND elicited by activation of all afferents whose primary site of termination is in the NTS.…”
mentioning
confidence: 68%
See 4 more Smart Citations
“…Specifically, blockade of N-methyl-Daspartate (NMDA) receptors in the LTF significantly reduced baroreceptor-mediated inhibition of SND and the cardiacrelated rhythm in SND (26), whereas blockade of non-NMDA EAA receptors reduced the increases in SND produced by activation of arterial chemoreceptors and electrical stimulation of afferents in the cervical vagus nerve (27). Also, we showed that chemical inactivation of the LTF with microinjection of muscimol eliminated the component of SND time-locked to intratracheal pressure (ITP, an index of vagal lung inflation afferent activity) without disrupting the entrainment of phrenic nerve activity (PNA) to ITP (29). These data led us to postulate that the LTF was involved in mediating changes in SND elicited by activation of all afferents whose primary site of termination is in the NTS.…”
mentioning
confidence: 68%
“…As was the case in earlier studies (26,29), we maintained mean arterial pressure (MAP) at approximately the same level throughout the experiment by adjusting the rate of an intravenous infusion of a mixture of dextran and saline. This was done to maintain a reasonably stable level of baroreceptor afferent nerve activity.…”
Section: General Proceduresmentioning
confidence: 99%
See 3 more Smart Citations